Output-based allocation and investment in clean technologies - Knut Einar Rosendahl; Halvor Briseid Storrøsten (Statistics Norway, Research Department, 2011)
Allocation of emission allowances may affect firms' incentives to invest in clean technologies. In this paper we show that so-called output-based allocation tends to stimulate such investments as long as individual firms do not assume the regulator to tighten the allocation rule as a consequence of their investments. The explanation is that output-based allocation creates an implicit subsidy to the firms' output, which increases production, leads to a higher price of allowances, and thus increases the incentives to invest in clean technologies. On the other hand, if the firms expect the regulator to tighten the allocation rule after observing their clean technology investment, the firms' incentives to invest are moderated. If strong, this last effect may outweigh the enhanced investment incentives induced by increased output and higher allowance price.
Keywords: H21; Q58; 330; Emissions trading; allocation of quotas; abatement technology.